2019
DOI: 10.3390/socsci8030075
|View full text |Cite
|
Sign up to set email alerts
|

Survey Study on Attitudes to Multi-Dimensional Sustainable Development with U.K. MSc Students

Abstract: As reflected in the sustainable development goals (SDGs), sustainable development is a multi-dimensional concept integrating political, ethical, economic, and other factors. Reports from the United Nations (UN) Decade of Education for Sustainable Development (UNDESD) suggest that universities are more engaged with sustainable development in higher education. Despite promising signals about student awareness of sustainable development, survey studies suggest student engagement and knowledge is limited. Previous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…It educates farmers on how to increase the agricultural produce via accurate planning that reduces the cost and increases the product, in addition to keeping the environment through proper disposal of waste and packaging consumables and participating in vaccination campaigns against Epidemic diseases. In brief, these results corroborate the results of (e.g., Carter & Marx, 2016;Devereux, 2008;Measham & Barnett, 2008;Melles, 2019) in relation to the fact that the environmental issue and its protection has been a main and intrinsic dimension in sustainable development which cannot be established on weak resources. The environment cannot be protected when there is no development and so governments alone cannot establish sustainable development without voluntary participation to play a significant role in education and development of environmental awareness and modification of developmental conduct.…”
Section: Discussionsupporting
confidence: 86%
“…It educates farmers on how to increase the agricultural produce via accurate planning that reduces the cost and increases the product, in addition to keeping the environment through proper disposal of waste and packaging consumables and participating in vaccination campaigns against Epidemic diseases. In brief, these results corroborate the results of (e.g., Carter & Marx, 2016;Devereux, 2008;Measham & Barnett, 2008;Melles, 2019) in relation to the fact that the environmental issue and its protection has been a main and intrinsic dimension in sustainable development which cannot be established on weak resources. The environment cannot be protected when there is no development and so governments alone cannot establish sustainable development without voluntary participation to play a significant role in education and development of environmental awareness and modification of developmental conduct.…”
Section: Discussionsupporting
confidence: 86%
“…Lévesque (2013) argues the shared responsibility between the public and private sectors, requiring uprooting the myth of innovation as an activity tied to enterprise organizations. This emphasizes the role of the state in the undertaking of social change and of the participation of the other social institutions in the framework of the advance in the sustainable development of territories (Melles 2019) through applied solutions such as the diversification of sectors, generation of responsible technologies, and the opportunity for growth and community advancement.…”
Section: Social Innovation: a Conceptualizationmentioning
confidence: 99%
“…To carry out this search, the Web of Science database was basically used, searching for different combinations of terms such as "Sustainable Development Goals", "SDG", "Survey", Questionnaire", "Perception", "University students", or "Awareness". Some works have been found that use surveys regarding the SDGs in different university environments [2,3,4,6,7,8,9,10]. But for the most part they are focused on knowing the degree of knowledge of the SDGs [2,7,10], and their degree of implementation, attitudes or actions adopted by Universities [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…Some works have been found that use surveys regarding the SDGs in different university environments [2,3,4,6,7,8,9,10]. But for the most part they are focused on knowing the degree of knowledge of the SDGs [2,7,10], and their degree of implementation, attitudes or actions adopted by Universities [8,9]. Therefore, these surveys and their main objective are different from the approach that we try to give in this work, in which we try to find out mainly what is the perception that students have regarding the SDGs, and to a lesser extent, also what is the degree of awareness they have about them.…”
Section: Methodsmentioning
confidence: 99%